1986
DOI: 10.1039/c39860001580
|View full text |Cite
|
Sign up to set email alerts
|

Control of Si–C bond cleavage at carbon α to phosphorus. Suppression of facile protodesilylation of PPh2CH2SiMe2H by complexation through phosphorus to ruthenium and the X-ray crystal and molecular structure of [Ru(η6-p-cymene)Cl2(PPh2CH2SiMe2OH)]

Abstract: Facile cleavage of the Si-C bond a t o P in Ph2PCH2SiMe2H which is induced by HY (Y = OH, OMe, or CI) is suppressed on complexation at Ru in [Ru(q6-cym)CI2( PPh2CH2SiMe2H)] (cym = p-cymene); instead the latter reacts where Y = OH t o afford the silanol complex [Ru(q6-cym)CI2(PPh2CH2SiMe2OH)] which has been structurally characterized by X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…measurements revealed that complex (9) was obtained as a mixture of isomers (9a) and (9b) in variable relative proportions (see above). Complexes (6)-- (8) were obtained by the same method.…”
mentioning
confidence: 99%
“…measurements revealed that complex (9) was obtained as a mixture of isomers (9a) and (9b) in variable relative proportions (see above). Complexes (6)-- (8) were obtained by the same method.…”
mentioning
confidence: 99%
“…112 Slow crystallization from wet acetone of a mixture of [{RuCl 2 (T|-cym)} 2 ] and Ph 2 PCH 2 SiMe 2 H gives the phosphino-silanol complex [RuCl 2 (PPh 2 CH 2 SiMe 2 OH)(r|-cym)]*, whereas free Ph 2 PCH 2 SiMe 2 H is rapidly cleaved by protic agents to Ph 2 PMe. 113 The diastereomers formed by reaction of (+)-neomenthyldiphenylphosphine with [{RuCl 2 (r|-o-MeC 6 H 4 CO 2 Me)}2] can be separated by fractional crystallization; the less soluble diastereomer has the (R) configuration at the chiral planar unit. The separated diastereomers are converted into the enantiomeric (R,R) and (S,S) forms o f [ { R u C l 2 ( r j -6 > -MeC 6 H 4 CO 2 Me)} 2 ] by heating with cod in propan-2-ol and subsequent treatment of the cod complexes with HC1.…”
Section: Derivatives With Co Rnc and Prmentioning
confidence: 99%
“…Solid state silanol structures which do not involve any hydrogen bonding are known but are comparatively rare. 7 Thus, intermolecular hydrogen bonding in silanols has been extensively studied and shown to take many forms. 8 For example, diisopropylsilanediol, 9 exists as hydrogen bonded dimers which are linked together in ladder chains by further hydrogen bonds, and tris(trimethylsilyl)silylsilanetriol 10 forms hexameric cages of hydrogen bonds.…”
mentioning
confidence: 99%